Mestika Zed Work Somewhere In The Jungle, Pemerintahan Darurat Republik Indonesia and its Meaning for the History of PDRI and PDRI Figures in the History of the Nation - Fajri, Ahmad; Asnan, Phil Gusti; Zulqaiyyim, Zulqaiyyim (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aims to see the effects of the book Mestika Zed Somewhere in the Jungle, The Emergency Government of the Republic of Indonesia directly or not, give a big contribution to the recognition of the government of Indonesia on the role of the PDRI in the history of the Indonesian nation. This study was conducted using 4 stages of historical research. The first is the heuristic stage collection in the form of books, articles, etc. The second source of criticism is testing data by conducting internal and external criticism of the authenticity of the data obtained. The third interpretation is the interpretation of data so that it becomes a meaningful fact. The final stage is the writing of history in the form of a thesis. The results showed after the publication of the book Somewhere in the Jungle, The Emergency Government of the Republic Indonesia, the works of the PDRI more and more written, such as works Amrin Imran was PDRI dalam Perang Kemerdekaan. Pdri birthday setting as HBN, one of them is thanks to the services of historian Mestika Zed. Proposal national hero candidate PDRI figure Syafruddin Prawiranegara also Mestika Zed involved in it.